1993
DOI: 10.1007/bf01108411
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of OprB, a glucose-inducible porin ofPseudomonas aeruginosa

Abstract: OprB, a glucose-inducible porin of P. aeruginosa, was characterized by black lipid bilayer analysis and circular dichroism spectroscopy. Black lipid bilayer analysis of OprB revealed a single-channel conductance of 25 pS, the presence of a glucose binding site with a Ks for glucose of 380 +/- 40 mM, and the formation of channels with a strong selection for anions. Analysis of P. aeruginosa OprB circular dichroism spectra revealed a high beta sheet content (40%) which is within the range of that determined for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…It has also been shown that there is active transport of pyruvate across the cytoplasmic membrane in E. coli but not in Pseudomonas (41). Glucose, in contrast, is taken up very efficiently by P. aeruginosa (13,67,73). In E. coli, expression of PDH genes is regulated by a pyruvate-sensitive repressor, PdhR (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that there is active transport of pyruvate across the cytoplasmic membrane in E. coli but not in Pseudomonas (41). Glucose, in contrast, is taken up very efficiently by P. aeruginosa (13,67,73). In E. coli, expression of PDH genes is regulated by a pyruvate-sensitive repressor, PdhR (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Although the single-channel conductance of OpdH was on average 10 times greater than those of other characterized specific porins of Pseudomonas species, it is considered small compared to those of OmpF and OmpC, the major porins of E. coli (0.23 nS versus 1 to 2 nS) (9,23,25,38,57). Also, of the many compounds that were tested as potential substrates for OpdH, significant growth defects were observed only for two compounds: isocitrate and cis-aconitate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses, including the induction of OprB by growth on glucose (10), the demonstration of facilitated diffusion of glucose into liposomes containing OprB (30), and the verification of a glucose binding site in OprB (35), suggested that OprB would form a glucose-selective porin in the outer membrane of P. aeruginosa. The results presented here verify that in vivo, OprB does facilitate the diffusion of glucose into the cell.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of proteins by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) used the 11% (wt/vol) gel system of Lugtenberg et al (17). The production of polyclonal antibodies specific for heat-modified OprB and immunodetection protocols have been previously described (35). Bacterial cell envelopes were prepared by the method of Lugtenberg et al (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation